2022
DOI: 10.3389/fmed.2021.728521
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Prediction Model for Acute Renal Failure After Acute Aortic Syndrome Surgery

Abstract: BackgroundAcute renal failure (ARF) is the most common major complication following cardiac surgery for acute aortic syndrome (AAS) and worsens the postoperative prognosis. Our aim was to establish a machine learning prediction model for ARF occurrence in AAS patients.MethodsWe included AAS patient data from nine medical centers (n = 1,637) and analyzed the incidence of ARF and the risk factors for postoperative ARF. We used data from six medical centers to compare the performance of four machine learning mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…[ 10 , 11 , 26 ] Although the XG Boost algorithm is known to exhibit better performance than other algorithms, it requires more time for model training. [ 25 , 27 ] Our study demonstrated a good classification performance with only hyperparameter tuning through Grid Search CV, without using XG Boost or gradient boosting tree algorithms.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[ 10 , 11 , 26 ] Although the XG Boost algorithm is known to exhibit better performance than other algorithms, it requires more time for model training. [ 25 , 27 ] Our study demonstrated a good classification performance with only hyperparameter tuning through Grid Search CV, without using XG Boost or gradient boosting tree algorithms.…”
Section: Discussionmentioning
confidence: 87%
“…The SHAP method intuitively shows the contribution of each feature and is effective in determining the importance of individual features. [ 11 , 25 ] The confusion matrix was categorized into 4 groups based on the classification outcome and is most commonly used for evaluating binary classifiers. [ 11 ] The F1 score is the harmonic mean of precision and recall.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we utilized machine learning to ascertain whether these 20 hub genes can construct a comprehensive prognostic model. XGBoost algorithm, a popular algorithm in machine learning classifiers that has demonstrated excellent performance ( 28 ), was selected for generating the model based on those 20 hub genes. In order to improve the model, XGBoost calculates negative gradients and uses them to find problems.…”
Section: Resultsmentioning
confidence: 99%
“…There were 1,909 articles identified [Cochrane ( n = 133), PubMed ( n = 33), Embase ( n = 231), Web of Science ( n = 1,512)]. After removing 220 duplicates, titles and abstracts of the remaining 1,689 articles were browsed, and 38 studies ( 12 49 ) were finally included. A PRISMA flow diagram of the study selection process is shown in Supplementary File 4 .…”
Section: Resultsmentioning
confidence: 99%
“…These were 60 prognostic models for CSA-AKI included, 12 external validation models, and 7 random sampling validation models. The types of these 60 prognostic models include: Logistic Regression ( 12 16 , 19 22 , 24 35 , 37 49 ) ( n = 34), Neural Net ( 15 , 17 19 ) ( n = 6), Support Vector Machine ( 15 , 16 ) ( n = 4), Random Forest ( 15 , 16 , 30 , 40 ) ( n = 6), Extreme Gradient Boosting ( 15 , 16 , 49 ) ( n = 3), Decision Tree ( 15 , 16 ) ( n = 3), Gradient Boosted Machine ( 19 ) ( n = 1), COX regression ( 19 ) ( n = 1), κ Neural Net ( 19 ) ( n = 1), and Naïve Bayes ( 19 ) ( n = 1). Characteristics of included studies are shown in Supplementary File 1 .…”
Section: Resultsmentioning
confidence: 99%